The Composition of Surety - Bagdžius, Justinas (Teisė, 2022)
The article analyzes the legal institutionalization of surety as a social phenomenon as well as the reasons that led to its emergence and formation. The article tries to look at suretyship from a civil and criminal legal point of view in a comparative aspect, trying to form an unrefined concept of suretyship as an institute of criminal law.